Seismic response of reinforced concrete moment-resisting frame with steel damper columns under earthquake sequences: evaluation using extended critical pseudo-multi impulse analysis - Fujii, Kenji (Frontiers in Built Environment, 2025)
In major seismic events (e.g., the 2011 Tohoku-Taiheiyou-Oki Earthquake, the 2016 Kumamoto Earthquake in Japan, and the 2023 Kaharamanmaraş Earthquake in Turkey), many building structures are subjected to a series of earthquake sequences. Therefore, evaluating the seismic demands of building structures under earthquake sequences is important. This article proposes extended critical pseudo-multi impulse (PMI) analysis considering sequential input. In this extended PMI analysis, seismic input is modeled as two parts of multi impulses (MIs). The parameters of the seismic input are (a) the pulse velocities of the first and second MIs, (b) the number of impulsive lateral forces of the first and second MIs, and (c) the length of the interval between the two MIs. In the numerical analysis, the peak and cumulative responses of an eight-story reinforced concrete (RC) moment-resisting frame (MRF) with steel damper columns (SDCs) subjected to the earthquake sequence recorded during the 2016 Kumamoto Earthquake were predicted using the proposed extended critical PMI analysis. For this prediction, the pulse velocities of the first and second MIs were determined based on the maximum momentary input energy of the input ground motions. The main findings are as follows. (1) The accuracy of the predicted peak response of RC MRFs with SDCs subjected to earthquake sequences from the extended critical PMI analysis was satisfactory. (2) The accuracy of the cumulative response of RC MRFs with SDCs depended on the ground motion records and the number of impulsive lateral forces of the first and second MIs.